2022
DOI: 10.1002/mrm.29501
|View full text |Cite
|
Sign up to set email alerts
|

Childhood to adulthood: Accounting for age dependence in healthy‐reference distributions in 129Xe gas‐exchange MRI

Abstract: Purpose Xenon‐129 (129Xe) gas‐exchange MRI is a pulmonary‐imaging technique that provides quantitative metrics for lung structure and function and is often compared to pulmonary‐function tests. Unlike such tests, it does not normalize to predictive values based on demographic variables such as age. Many sites have alluded to an age dependence in gas‐exchange metrics; however, a procedure for normalizing metrics has not yet been introduced. Theory We model healthy reference values for 129Xe gas‐exchange MRI aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…We observed a clear age-related decrease in the RBC:M ratio, as also observed by Plummer et al ( 20 ) and strikingly similar to the preliminary results reported by Collier et al ( 22 ), who estimated an age coefficient of −0.004/yr. vs. our finding of −0.005/yr.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed a clear age-related decrease in the RBC:M ratio, as also observed by Plummer et al ( 20 ) and strikingly similar to the preliminary results reported by Collier et al ( 22 ), who estimated an age coefficient of −0.004/yr. vs. our finding of −0.005/yr.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work by Plummer et al has sought to address this gap by modeling age-related changes in 129 Xe image intensity histograms, with the goal of creating a tailored reference histogram for a given set of patient attributes ( 20 ). Here, we take an alternative approach ( 21 ) akin to that adopted by Collier et al ( 22 ) and use multivariate linear models to evaluate age-related changes in 129 Xe MRI and spectroscopy, including the RBC:M, RBC:Gas, Mem:Gas, RBC chemical shift, and RBC amplitude oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using dynamic spectroscopy with multichannel receive coils presents a promising avenue of providing modest localization of oscillations without the types of artifacts that affect the key‐hole approach used here 39 . Future work would benefit from the incorporation of additional relevant demographic/clinical information, such as fingertip optical hemoglobin measurements, 40 age, 41 weight, and height, into the reference distribution. Although this work demonstrated that RBC oscillation heterogeneity is prevalent in patients with CTEPH and improved by PTE surgery, the spatial accuracy with which regions of low RBC oscillations can be localized remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A GAMLSS was used to estimate VZV-IgG reference values and draw centile charts [ 13 , 14 , 15 ]. The GAMLSS requires a parametric distribution assumption for the response variable and models the distribution function of the explanatory variables using a nonparametric smoothing function, making the GAMLSS a semi-parametric regression type model [ 16 ] with the formula shown below: where μ represents the mean, σ represents the variance, υ represents the skewness, and τ represents the kurtosis.…”
Section: Methodsmentioning
confidence: 99%